Crimes agrários e da proteção estatal do campesino no Brasil: da (in)aplicabilidade da teoria do domínio do fato na punição dos mandantes de homicídios no meio rural - Souza, Cristiano de Freitas (2024)
In Brazil, there are several conflicts over possession and ownership of land, which are presented for the occurrence of crimes, among them, homicide committed against people living in rural areas, when the action comes from the order of a principal to commit the crime. In this sense, the objective was to analyze the rules related to the competition of people described in art. 29, of the Penal Code, verifying whether they are sufficient to prevent and reprove criminal injustice, as well as the possibility of applying the theory of mastery of the fact in cases of “pistoling” or “mercenary homicide” in the field. In this context, it has become relevant to know the historical factors behind the formation of agrarian property and its effects today, and whether or not these facts are contributory elements to the existence of various disputes over areas, in addition to the occurrence of crimes due to issues related to Earth. Furthermore, the intention was to verify whether the characterization of the peasant as an enemy is an instrument for maintaining the dominant elite and dominating the excluded as a strategy of capital. In this sense, emblematic cases that occurred on national soil and current data on violence in the field of the Pastoral Land Commission, specifically those referring to the period from 2017 to 2022, prove the thematic relevance of this study, as the intention is to create alternatives to reduce criminal offenses in the agricultural sphere and, consequently, preserve lives, through a regulatory system that aligns criminal norms with effective public policies on access to land, which can lead to a reduction in homicides. It is observed that when the figure of the “land-invading enemy” was created, the consequence was his elimination from the “good society”, the loss of citizenship, privileging the interests of landowners and rural entrepreneurs. And, within the scope of criminal law effectiveness, it was noted that there are several theories about the concurrence of people, without, however, resolving the problem of indirect authorship. And, added to this, the theory of mastery of fact cannot be used in all cases of mediate authorship; as well as the lack of consensus in the jurisprudence of the Superior Court of Justice on the possibility of applying the qualifier of art. 121, § 2o, I, of the Penal Code, to the principal, and the ineffectiveness of the Jury Court procedure, demonstrate the need to change the Penal Code, to objectively provide for the rules on indirect authorship, and the Criminal Procedure Code, to improve the judgment of crimes of manslaughter in rural areas